“Honestunes”: Video Musik Kolaborasi Virtual di Masa Pandemi - Sahertian, Grace Carolline (Serat Rupa: Journal of Design, 2023)
The arts and entertainment industry is one of the industries that have been heavily impacted by the Covid-19 pandemic. At the beginning of the pandemic, many musicians lost their stages and musical works that could not be promoted optimally, especially with the implementation of social distancing protocols and large-scale social restrictions. In this "new normal" era, musician Grace Sahertian invites her listeners to participate in making the music video for "Honestunes." The main videos, video footage, and videos posted by netizens will be packaged with a touch of illustrations and attractive graphics using motion graphics techniques, giving the impression of being fun, playful, and lighthearted. It is hoped that this virtual collaboration can be an alternative to video work for music promotion in the midst of a pandemic. Additionally, this video clip can also be used as a reference for musicians and the public to adapt to the digital world.